British Archaeology Abroad, 1964: British Institute of Persian Studies at Tehran - Stronach, David
Excavations at Pasargadae; exploration of Palaeolithic and Mesolithic cave deposits between Meshed and Behshahr (Ali Tappeh); field survey in Luristan.